ANALYSIS OF RADEC LEARNING MODEL ON TRIBAL AND HEALTH CONCEPTS ON SCIENCE LITERACY - Muh Hasbi; Khaeruddin Khaeruddin; Ma'ruf Ma'ruf (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
This study aims to analyze the radec learning model for scientific literacy and learning outcomes. The type of research used in this study is Quantitative research (quasi experiment). The subjects used in this study were students of class V with a total of 70 students consisting of two classes (VA and VB). The instruments used in this study were in the form of instruments, namely tests, questionnaires, observation and documentation. Data analysis techniques were carried out, namely descriptive tests (mean, median, mode and standard deviation) and inferential tests (Normality, Homogeneity and Manova).. Based on data analysis using SPSS 25 that tests the normality of cyan literacy and learning outcomes usingKolmogorov-Smirnovi.e. sig 0.05 from the pretest and posttest results of the control and experimental classes and the homogeneity test using the based mean is sig 0.05 from the pretest and posttest results of the control and experimental classes while the manova test is obtained showing a significance value of 0.000. 0.000 0.05 then Ho rejected and Ha accepted. Based on this, it can be concluded that there is a significant influence on the use of the Learning ModelRadec on scientific literacy and science learning outcomes UPT SPF SDI Bontoa Makassar.